2010
DOI: 10.1002/pds.2007
|View full text |Cite
|
Sign up to set email alerts
|

“Save 30% if you buy today”. Online pharmacies and the enhancement of peripheral thinking in consumers

Abstract: Our results show that OPs advertise their products in an argumentative fashion that enhances consumers' peripheral reflection: by analogically playing with the selling of other commodities, they magnify aspects of the online trade that consumers might find convenient, but overshadow the nature and risks of the actual products they sell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…In 2003 Arruanda [58] found that their sample was equally divided into 3 groups: selling 1 drug only, between 2 and 29 drugs (average 7), and selling 30 or more. The various studies reported several specific drug offers: sildenafil [59,60,80,84,86,87], benzodiazepines [84,86,87], painkillers [80,84,88], antibiotics [87,88], insulin [87,88], female hormones [87,88], antidepressants [80,84,86], alopecia medications [14,27,80], and obesity medications [59,80]. Bloom and Iannacone [62] reported that 160 separate medications were offered in their sample, which gives an idea of how widely differentiated the drug offer is.…”
Section: Resultsmentioning
confidence: 99%
“…In 2003 Arruanda [58] found that their sample was equally divided into 3 groups: selling 1 drug only, between 2 and 29 drugs (average 7), and selling 30 or more. The various studies reported several specific drug offers: sildenafil [59,60,80,84,86,87], benzodiazepines [84,86,87], painkillers [80,84,88], antibiotics [87,88], insulin [87,88], female hormones [87,88], antidepressants [80,84,86], alopecia medications [14,27,80], and obesity medications [59,80]. Bloom and Iannacone [62] reported that 160 separate medications were offered in their sample, which gives an idea of how widely differentiated the drug offer is.…”
Section: Resultsmentioning
confidence: 99%
“…"discount" (all adjectives and "selling arguments" identified as used by online sellers) were then extracted for further analysis to identify specific characteristics of the seller/marketplace [41].…”
Section: Figure 1: Summary Of Study Methodologymentioning
confidence: 99%
“…For example, although this criminal activity is perpetrated by a host of clearly criminal actors (e.g., illegal manufacturers, organized crime, illicit online pharmacies), others, including Internet Service Providers (e.g., search engines, social media platforms, hosting companies, payment processors, affiliate sites, transportation companies, etc. ), enable illicit online pharmacy operations but often span multiple jurisdictions and legal regimes (including those that may be exempt from liability) [19-21,44] (See Figure 1). This patchwork of various illicit and legal actors makes it difficult to detect, prevent and engage in enforcement efforts against illicit online pharmacies at the domestic level, consequently requiring global coordination and cooperation that is elusive without effective multistakeholder governance [20,22].…”
Section: Internet Pharmacy Governance and Enforcement Effortsmentioning
confidence: 99%
“…Illicit online pharmacies market the sale of purportedly safe, legitimate product that may in fact be counterfeit or of substandard quality [15,19-21]. This activity should not be conflated with the global debate over the appropriate definition of “counterfeit” medicines, which is currently mired in considerations involving intellectual property rights and access to medicines [22].…”
Section: Introductionmentioning
confidence: 99%